Thematic analysis of Diwān-e-abī ṭālib in the perspective of the Qur’an and the Sunnah - Kanwal, Shamsa; Al-Azhari, Dr. Ali Akbar (Al-Irfan, 2025)
This article is a thematic exploration of Diwān-e-Abī Ṭālib, a collection of poetry attributed to Ḥadrat Abu Ṭālib ibn ʿAbd al-Muṭṭalib, who was the uncle and protector of the Holy Prophet PBUH. Besides its historical and theological significance, Diwān-e-Abī Ṭālib contains multiple and multidimensional themes in it. This research fills a fundamental gap through a comprehensive analysis of the themes conveyed in his poetry, while aligning them with Qur’anic teachings and the Sunnah. The Qualitative approach and descriptive mode of expression have been employed for the thematic analysis. There are various themes in Diwān-e-Abī Ṭālib, but this study focuses only on foundational Islamic themes, including monotheism (Tawḥīd), support for the Prophet and the Prophethood (Risālah), his moral excellence, noble lineage of the Holy Prophet PBUH, and righteous religion. This research concludes that the Diwān-e-Abī Ṭālib is not merely a collection of poetry depicting the Islamic history, rather it conveys the fundamental message of Islam through its sublime themes. It offers further research of multifaceted dimensions of Diwān-e-Abī Ṭālib.